Komunikasi Simbolik Dalam Upacara Ritual Hudoq Suku Dayak Bahau Umaq Luhat Desa Kelian Luar Kabupaten Kutai Barat Kalimantan Timur - Geroda, Elvis Deventus; Prima, Edelweis Puti (DIGICOM : Jurnal Komunikasi dan Media, 2024)
The importance of understanding symbolic communication in the Hudoq ritual ceremony is an effort for the people of the Dayak Bahau Umaq Luhat tribe, Kelian Luar Village, to preserve the traditional art of the Hudoq ritual left by their ancestors. So that this ability becomes something unique, as well as an attitude of respect for the life values left by our ancestors. In essence, this research aims to find out the symbolic communication behind the Hudoq ritual in the Dayak Bahau Umaq Luhat tribe, Kelian Luar Village, Long Iram District, West Kutai Regency, East Kalimantan. Examining the Communication Symbols, the overall meaning of the symbols in 1). The effectiveness of symbolic communication in the Hudoq Ritual for the people of Kelian Luar Village, because the Hudoq Dance Ritual has a symbolic meaning for the success of harvesting rice, as well as a feeling of fear if the ritual is not carried out. This type of research is qualitative descriptive using an anthropological approach, and the symbolic interactional theory introduced by Herbert Blumer is a derivative of George Herbert Mead's thoughts in the scope of sociology, which states that communication takes place through the exchange of symbols and the meaning of these symbols, and by using data analysis techniques, data reduction, data presentation and drawing conclusions. The results of this research are; 1). The birth of the Hudoq ritual is a form of Sangaji religious belief. 2). The function of the Hudoq ritual ceremony is a form of communication with the spirits of ancestors. 3). The various movements in the presentation symbolize a form of respect, a prayer of hope and protection to the ancestors. 4). Dancer costumes made from banana leaves and areca nuts mean immortality, safety, fertility and success. 5). The Hudoq mask is a sacred mask in the Hudoq ritual ceremony of the Dayak tribe.